The ABC Bicuspid Sizing Protocol for SAPIEN 3 Balloon-Expandable Valves - Tej Sheth, MD; Umar Ismail, MD; Jorge Chavarria, MD; Warkaa Al Shamkani, MD; Ahmed Makhdoum, MD, MSc; Kandace Forsyth, MSc; Iqbal Jaffer, MD, PhD; James Velianou, MD; Madhu Natarajan, MD, MSc (Structural Heart)
Background: The computed tomography selection of patients with bicuspid aortic stenosis for treatment with balloon-expandable valve (BEV) transcatheter aortic valve replacement (TAVR) is uncertain. We therefore evaluated a novel sizing algorithm for SAPIEN 3 BEV. Methods: A prospective single-center registry from February 2020 to May 2024 including patients with bicuspid aortic stenosis treated with TAVR (and surgical aortic valve replacement starting in September 2022). TAVR patients were treated according to the ABC bicuspid sizing algorithm with criteria for annular area (<10% oversizing or <5% with calcification), below annular (left ventricular outflow tract [LVOT]) area (<10% oversizing or <5% with calcification), intercommissural distance (>planned valve diameter - 1 mm), maximum sinus diameter (>planned valve diameter + 6 mm), and avoidance of high-risk leaflet calcification. The study endpoints were technical success and device success at 30 days. Results: From February 2020 to May 2024, 106 patients were treated with TAVR, and (from September 2022) 10 patients were treated with surgical aortic valve replacement due to inadequate sinus dimensions for TAVR or the presence of high-risk calcium. Among TAVR-treated patients, final valve sizing was determined by annular area in 77.5%, LVOT in 21.7%, and intercommissural distance in 1.9%. Most changes (84%) involved reducing planned valve diameter, resulting in modest final annular (1.032%) and LVOT (1.042%) oversizing. Technical success was obtained in 105 (99%) patients, and device success at 30 days in 102 (96.2%) patients. Conclusions: A dedicated sizing algorithm for BEVs was able to select patients for BEV with very high device success.